A MAXIMAL PREDICTABILITY PORTFOLIO SUBJECT TO A TURNOVER CONSTRAINT - TAKAYA, YOSHIHIRO; KONNO, HIROSHI (Asia-Pacific journal of operational research, 2010)
The authors demonstrated in earlier papers that a maximal predictability portfolio (MPP) using a dynamic strategy leads to a significantly better ex-post performance than the one based on a static strategy and the index. In this paper, we will consider a maximal predictability portfolio subject to transaction cost. To reduce transaction cost, we employ turnover constraint. It will be shown that this approach leads to a significantly better performance than the standard MPP and the index.